The 1921 Constitution and Beyond: Any Inspiration After 100 Years? - Nilay Arat; Aslı Topukçu (Annales de la Faculté de Droit d’Istanbul)
The 1921 Constitution has mostly been considered as a unique piece of legal document in Turkish Legal History with regard to the time it was written, the conditions under it was created, the necessity it touched and the era it changed. The 1921 Constitution had been assessed by scholars, bureaucrats, politicians and lawyers in different times from distinct perspectives. It has got special attention lately as regards to the discussions on constitution-making processes. Even after 100 years, many of its features inspire today’s constitutional discussions as the 1921 Constitution touches even today’s sociological, political and legal needs. In this context, this paper aims to assess the 1921 Constitution first by pointing out the unique features; then, gives try to answer a question posed whether the 1921 Constitution is a constitution itself, or not. This trial is done under the double constitution period discussions and by pulling out the deficiencies of the 1921 Constitution. Subsequently, the box of inspirational touches of the 1921 Constitution to 100 years beyond is opened. In that sense, it has been found that the understanding of sovereignty that brings it down to its origin “earth/humankind”, the idea of local democracy and the vision on fundamental rights and freedoms that open the door to modern understanding of rights on this part of the world, could be drawn/inherited for today’s constitutional making processes.